Genome editing of crops: A renewed opportunity for food security - Georges, Fawzy; Ray, Heather (GM crops & food, 2017)
Genome editing of crop plants is a rapidly advancing technology whereby targeted mutations can be introduced into a plant genome in a highly specific manner and with great precision. For the most part, the technology does not incorporate transgenic modifications and is far superior to conventional chemical mutagenesis. In this study we bring into focus some of the underlying differences between the 3 existing technologies: classical plant breeding, genetic modification and genome editing. We discuss some of the main achievements from each area and highlight their common characteristics and individual limitations, while emphasizing the unique capabilities of genome editing. We subsequently examine the possible regulatory mechanisms which governments may be inclined to use in assessing the status of genome edited products. If assessed on the basis of their phenotype rather than the process by which they are obtained, these products will be categorized as equivalent to those produced by classical mutagenesis. This would mean that genome edited products will not be subject to the restrictions imposed on genetically modified products, except in some cases where the mutation involves a large sequence insertion into the genome. We conclude by examining the potential of societal acceptance of genome editing technology, reinforced by a scientific perspective on promoting such acceptance.